IMPLEMENTATION OF THE MAIN COLUMN STRUCTURE USING THE FREESTANDING METHOD & STUDY OF LAP SPLICE CONNECTIONS ON THE GGM MAJALENGKA BUILDING PROJECT IN MAJALENGKA DISTRICT - purwati, Nabila aisya; Rijaluddin, Arief (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2024)
The GGM Building is a circular sports building, has 2 floors with circular columns. Columns are the most important structural part for a building to stand. In accordance with SK SNI T-15-1991-03 what is meant is a building structural component column whose main task is to support axial, compressive and vertical loads. In this report study, the method used for the main column reinforcement work is Free Standing which can be interpreted as a structure that is strong and stands upright. The GGM Building is a high-rise building which of course has a structure that can stand perfectly upright at any height. The type of connection used in column cuttings is a contact lap splice which is a passing connection between two reinforcing bars that touch each other and are tied with concrete wire. SAP2000 software is used to analyze the values ​​of the forces acting on the main structural columns. Based on the results of analysis of the main structural columns using SAP 2000, the load distribution value was obtained, namely 22.81 KN/m with an axial force value of -229.220 KN for column type K1-1. 27.14 KN/m with an axial force value of -272.97 KN for column K1-2 and 31.86 KN/m with an axial force value of -320,150 KN for column K2. Then with manual calculations related to the self-load value of the main structural columns, namely 1,189.56 KN in column K1-1, 1,614.14 KN in column K1-2 and 1,981.11 KN in column K2. Keywords: column, lap splice, selfweight calculation, SAP 2000.